Perceived neighborhood environment and leisure time physical activity among adults from Curitiba, Brazil - Adriano Akira Ferreira Hino; Cassiano Ricardo Rech; Priscila Bezerra Gonçalves; Rodrigo Siqueira Reis (Universidade Federal de Santa Catarina, 2017)
The aim of this study was to analyze the association between perceived neighborhood characteristics and leisure time physical activity (PA) and the moderator effect of gender, age, schooling and time spent working/studying on perceived environment and leisure PA in adults. This is a cross-sectional study conducted with 699 adults (53.1% women), distributed from 32 census tracts selected according to walkability and neighborhood income characteristics in Curitiba. Perceived neighborhood characteristics were assessed using the Brazilian version of the Neighborhood Environment Walkability Scale-Abbreviated (A-NEWS). Leisure time PA was evaluated through the long-version IPAQ and walking and moderate to vigorous physical activity (MVPA) were analyzed separately. PA classification considered ≥10 minutes/week and ≥150 minutes/week of walking or MVPA. Associations were tested using a multilevel logistic binary model. After adjusting for potential confounders, aesthetics perception was associated with ≥10 minutes/week of walking. Additionally, access to public places for leisure remained associated with ≥10 minutes/week and ≥150 minutes/week of MVPA. The relationship between perceived access to public spaces, walking and MVPA were stronger in women and younger adults. It is concluded that a better perception of neighborhood aesthetics was associated with the practice of walking and access to public spaces with the practice of MVPA, respectively.